2018
DOI: 10.1007/s00592-018-1131-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening and diagnosis of gestational diabetes in India: a systematic review and meta-analysis

Abstract: Aims Although diabetes is rapidly increasing in India, there is no national consensus on best practices for screening, diagnosis, and management of gestational diabetes mellitus (GDM). The goal of this study was to systematically review the literature for studies reporting the prevalence and screening and diagnostic methods for gestational diabetes in India. Methods We searched MEDLINE, Embase, and POPLINE for studies on screening for GDM in India. We included English-language full reports and conference abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 80 publications
5
52
1
Order By: Relevance
“…16 Second, although no specific guidelines exist for assessing GD status in population-based and epidemiological surveys, there has been much debate regarding the optimal cutoffs to be used for screening and diagnosis of GD and the implications for pregnancy and neonatal outcomes. [39][40][41][42] weeks, and we had a roughly even distribution of women across trimesters of pregnancy. Our findings suggested that we were able to capture a similar proportion of women with elevated glucose in each trimester.…”
Section: Limitationsmentioning
confidence: 99%
“…16 Second, although no specific guidelines exist for assessing GD status in population-based and epidemiological surveys, there has been much debate regarding the optimal cutoffs to be used for screening and diagnosis of GD and the implications for pregnancy and neonatal outcomes. [39][40][41][42] weeks, and we had a roughly even distribution of women across trimesters of pregnancy. Our findings suggested that we were able to capture a similar proportion of women with elevated glucose in each trimester.…”
Section: Limitationsmentioning
confidence: 99%
“…Interestingly, Li et al found a large variation of Indian GDM estimates (0.0-41.9%) depending on the diagnostic criteria use. They conducted a meta-analysis of 64 studies reporting 90 prevalence estimates in India, and found using the IADPSG criteria resulted in significantly higher prevalence of 19.2% compared with WHO 1999 of 10.13% or DIPSI of 7.4% [36]. Similarly, Macaulay's systematic review published in 2014 of 6 countries in Africa estimated that the prevalence varied between 0% for Tanzania to 13.9% in Nigeria [18].…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes [6][7][8][9][10][11][12][13][14][15] For the diagnosis of gestational diabetes, oral glucose tolerance test (OGTT) was performed in several steps.…”
Section: Overt Hyperthyroidismmentioning
confidence: 99%
“…Fetal complications are premature birth, macrosomia, trauma during the birth, neonatal hypoglycaemia, perinatal death. 6,7 Gestational hypertension also referred to as pregnancy induced hypertension (PIH) is a condition characterized by high blood pressure during pregnancy. Hypertension during pregnancy affects about 6-8% of pregnant women.…”
mentioning
confidence: 99%